-139=-5(2k+7)-3k

Simple and best practice solution for -139=-5(2k+7)-3k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -139=-5(2k+7)-3k equation:


Simplifying
-139 = -5(2k + 7) + -3k

Reorder the terms:
-139 = -5(7 + 2k) + -3k
-139 = (7 * -5 + 2k * -5) + -3k
-139 = (-35 + -10k) + -3k

Combine like terms: -10k + -3k = -13k
-139 = -35 + -13k

Solving
-139 = -35 + -13k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '13k' to each side of the equation.
-139 + 13k = -35 + -13k + 13k

Combine like terms: -13k + 13k = 0
-139 + 13k = -35 + 0
-139 + 13k = -35

Add '139' to each side of the equation.
-139 + 139 + 13k = -35 + 139

Combine like terms: -139 + 139 = 0
0 + 13k = -35 + 139
13k = -35 + 139

Combine like terms: -35 + 139 = 104
13k = 104

Divide each side by '13'.
k = 8

Simplifying
k = 8

See similar equations:

| 49(y+3)+y=5y+12 | | 5x-9=(x-2) | | 7x+8y-16=0 | | 3.00=55b | | 20t+40= | | 120=5(3+x)+2x | | 4a-14= | | C=4x-2y | | 2(4-7)=7u+2-2(-5u-1) | | -12-12(8+5n)=8n+28 | | -16t^2+48t+36=0 | | 13.5-0.3k+2.5-0.8k=7-1.1k-8.4 | | 2x+8-6(x+1)=3x+7 | | 2(6d-3)=6(5+3D) | | y-0=-3(x-2) | | 2[4-(-4x-4)]=64x+72 | | 2a-5(a-2)+4(b-2)= | | a=1/2h(b1b2) | | 2[4-(4x-4)]=64x+72 | | (w-3)(w+1)= | | 2-3(x+4)=9-(3x-2) | | =x^2-2x-11 | | R+0.5=0.7 | | 4+8=6+2t | | 4(u+5)=-8u-40 | | -2(17x-4)+7(5x-7)-3=9-2 | | 7x+18=42x+11 | | -4(3x+5)=2(6-2x) | | -4x-4(1-2x)=7+4x | | 16x+5=10y | | (Q*0.33)+Q=72 | | 2(5y-7)+10=36 |

Equations solver categories